HUBUNGAN POLA MAKAN DAN AKTIVITAS FISIK DENGAN OBESITAS SENTRAL PADA USIA LANJUT DI INDONESIA: DATA RISET KESEHATAN DASAR - Dewanti Dewanti; Ahmad Syauqy; Etika Ratna Noer; ,Adriyan Pramono (GIZI INDONESIA, 2022)
The prevalence of central obesity in Indonesia increased from 2013 to 2018. The increased prevalence is related to changes in lifestyle. This study aimed to determine the relationship between dietary patterns and physical activity with central obesity among the elderly in Indonesia. This study used secondary data from the 2018 Basic Health Research (Riskesdas). Our study used a cross-sectional design. The population in this study was individuals aged 60 years and above with a total sample of 74,035. Data were analyzed using the Chi-square test and multiple logistic regression. Consumption of high sweet foods (OR:1,501, 95% CI:1,444-1,560), high sugary drinks (OR:1,372, 95% CI:1,313-1,433), high salty food (OR:1,322, 95% CI: 1,279-1,366), high fatty foods (OR:1,393, 95% CI:1,341-1,447), high baked foods (OR:1,239, 95% CI:1,197-1,283), high processed meat/chicken/fish with preservatives (OR:1,264, 95% CI:1,202-1,329), high seasonings (OR:1,226, 95% CI:1,178-1,276), high soft drink (OR:1,591, 95% CI:1,457-1,736), high energy drink (OR:1,498, 95% CI:1,356-1,654), high instant foods (OR:1,153, 95% CI:1,114-1,193), and low fruit vegetables (OR:1,598, 95% CI:1,542-1,657) had a significant relationship (p0.05) with central obesity separately. Physical activity had a significant association with central obesity (OR:1,215, 95%CI:1,172-1,261). Unhealthy and healthy dietary patterns and physical activity had significantly associated with central obesity among the elderly in Indonesia